Randomized controlled trials in children's heart surgery in the 21st century: a systematic review. (23rd November 2017) - Drury, Nigel E; Patel, Akshay J; Oswald, Nicola K; Chong, Cher-Rin; Stickley, John; Barron, David J; Jones, Timothy J
Abstract: OBJECTIVES: Randomized controlled trials are the gold standard for evaluating health care interventions, yet are uncommon in children's heart surgery. We conducted a systematic review of clinical trials in paediatric cardiac surgery to evaluate the scope and quality of the current international literature. METHODS: We searched MEDLINE, CENTRAL and LILACS, and manually screened retrieved references and systematic reviews to identify all randomized controlled trials reporting the effect of any intervention on the conduct or outcomes of heart surgery in children published in any language since January 2000; secondary publications and those reporting inseparable adult data were excluded. Two reviewers independently screened studies for eligibility and extracted data; the Cochrane Risk of Bias tool was used to assess for potential biases. RESULTS: We identified 333 trials from 34 countries randomizing 23 902 children. Most were early phase (313, 94.0%), recruiting few patients (median 45, interquartile range 28–82), and only 11 (3.3%) directly evaluated a surgical intervention. One hundred and nine (32.7%) trials calculated a sample size, 52 (15.6%) reported a CONSORT diagram, 51 (15.3%) were publicly registered and 25 (7.5%) had a Data Monitoring Committee. The overall risk of bias was low in 22 (6.6%), high in 69 (20.7%) and unclear in 242 (72.7%). CONCLUSIONS: The recent literature in children's heart surgery contains few late-phase clinical trials. Most trials did not conform to the accepted standards of reporting, and the overall risk of bias was low in few studies. There is a need for high-quality, multicentre clinical trials to provide a robust evidence base for contemporary paediatric cardiac surgical practice.